Meningkatkan Hasil Belajar Fisika Melalui Model Pembelajaran Kontekstual Tipe Problem Based Learning Pada Materi Gerak Lurus Kelas X SMA Negeri 37 Halmahera Selatan - Wulandari, Anisa; Mahyudin, Haryati (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2025)
This research is a classroom actionresearch that aims to improve the learning outcomes of students in class X S MA Negeri 37 South Halmahera Through the Application of Project Based Learning Model. The research method used is qualitative with the research location conducted in class X S MA Negeri 37 South Halmahera totaling 25 students. Data sources come from teachers and students. The data collection technique for this research is carried out in 2 cycles consisting of 4 components, namely: Planning, Observation, Evaluation and final teaching test. The data obtained were analyzed descriptively qualitatively. Based on the results of the study in class X at SMA Negeri 37 Halmahera Selatan on the learning outcome test from cycle 1 showed an increase compared to before being given learning by applying the Problem Based Learning learning model on Straight Motion material. After learning using the learning model, the results increased from 24% to 75%. In cycle II, the learning outcomes of students using the problem-based learning model increased by 100%. With an average value reaching 72.12%